Never Letting a Good Crisis Go to Waste: Canadian Interdiction of Asylum Seekers - Rehaag, Sean; Song, Janet; Toope, Alexander (Frontiers in Human Dynamics, 2020)
This article examines two moments of crisis at Canada's border with the United States: the aftermath of September 11th, 2001 (“9/11”) and the COVID-19 pandemic. The Canadian government leveraged both crises to offshore responsibilities for asylum seekers onto the United States. In the first case, Canada took advantage of U.S. preoccupations with border security shortly after 9/11 to persuade the United States to sign the Canada-U.S. Safe Third Country Agreement (“STCA”)—an agreement that allows Canada to direct back asylum seekers who present themselves at land ports of entry on the Canada-U.S. border. In the second case, Canada used heightened anxieties about international travel during the COVID-19 pandemic to persuade the United States to block irregular border crossings that asylum seekers were increasingly using to circumvent the STCA. After reviewing Canada's successful use of these moments of crisis to persuade the United States to take on additional responsibilities for asylum seekers for whom Canada would have otherwise been responsible, the article discusses a recent Canadian Federal Court decision that may make all this political maneuvering moot. This decision found that Canada cannot send asylum seekers back to the United States without violating constitutional rights to life, liberty, and security of the person. Given past practice, however, we can expect the Canadian government to continue to pursue avenues to persuade the United States to take on additional responsibility for asylum seekers—and moments of crisis will be important drivers for those efforts.